Analisis Strategi Bisnis PO. Selera Masa Dalam Menghadapi Persaingan - Tomy Muzaini; Nawazirul Lubis; Wahyu Hidayat (Universitas Diponegoro, 2015)
Selection of mode of transportation as one of the steps in the planning of transportation plays an important role in deciding policy issues in relation to the type of transport modes and infrastructure available. Research titled Effectiveness Analysis of Business Strategies PO. Selera Masa in Competition aims to determine the effectiveness of the business strategy undertaken by PO. Selera Masa on the present and examine the effectiveness of business strategies undertaken by PO. Selera Masa in the future.This type of research with descriptive method of research that seeks to said solving the problem based on the data in the field. The use of research methods with a SWOT analysis (Strengths, Weaknesses, Opportunities, Threats Analysis) is used to assist management in implementing the strategy which is expected to reveal the strategic issues of intensive, in-depth and comprehensive and formulate appropriate strategies in order to increase the accuracy of business strategies in PO. Selera Masa in the face of competition.